Prescription of glucose-lowering therapies and risk of COVID-19 mortality in people with type 2 diabetes: a nationwide observational study in England. Issue 5 (May 2021) - Khunti, Kamlesh; Knighton, Peter; Zaccardi, Francesco; Bakhai, Chirag; Barron, Emma; Holman, Naomi; Kar, Partha; Meace, Claire; Sattar, Naveed; Sharp, Stephen; Wareham, Nicholas J; Weaver, Andy; et al.
Summary: Background: In patients with type 2 diabetes, hyperglycaemia is an independent risk factor for COVID-19-related mortality. Associations between pre-infection prescription for glucose-lowering drugs and COVID-19-related mortality in people with type 2 diabetes have been postulated but only investigated in small studies and limited to a few agents. We investigated whether there are associations between prescription of different classes of glucose-lowering drugs and risk of COVID-19-related mortality in people with type 2 diabetes. Methods: This was a nationwide observational cohort study done with data from the National Diabetes Audit for people with type 2 diabetes and registered with a general practice in England since 2003. Cox regression was used to estimate the hazard ratio (HR) of COVID-19-related mortality in people prescribed each class of glucose-lowering drug, with covariate adjustment with a propensity score to address confounding by demographic, socioeconomic, and clinical factors. Findings: Among the 2 851 465 people with type 2 diabetes included in our analyses, 13 479 (0·5%) COVID-19-related deaths occurred during the study period (Feb 16 to Aug 31, 2020), corresponding to a rate of 8·9 per 1000 person-years (95% CI 8·7–9·0). The adjusted HR associated with recorded versus no recorded prescription was 0·77 (95% CI 0·73–0·81) for metformin and 1·42 (1·35–1·49) for insulin. Adjusted HRs for prescription of other individual classes of glucose-lowering treatment were as follows: 0·75 (0·48–1·17) for meglitinides, 0·82 (0·74–0·91) for SGLT2 inhibitors, 0·94 (0·82–1·07) for thiazolidinediones, 0·94 (0·89–0·99) for sulfonylureas, 0·94 (0·83–1·07) for GLP-1 receptor agonists, 1·07 (1·01–1·13) for DPP-4 inhibitors, and 1·26 (0·76–2·09) for α-glucosidase inhibitors. Interpretation: Our results provide evidence of associations between prescription of some glucose-lowering drugs and COVID-19-related mortality, although the differences in risk are small and these findings are likely to be due to confounding by indication, in view of the use of different drug classes at different stages of type 2 diabetes disease progression. In the context of the COVID-19 pandemic, there is no clear indication to change prescribing of glucose-lowering drugs in people with type 2 diabetes. Funding: None.